SOSIALISASI PENYULUHAN PENGENALAN CARA DAN MANFAAT MENABUNG SEJAK DINI PADA SISWA DAN SISWI SD 22 RANAH BATAHAN - Marwah; Yang Gusti Feriyanti; Muhammad Lutfi; Luckhy Natalia Anastasye Lotte; Arnes Yuli Vandika (Marsialapari: Jurnal Pengabdian Kepada Masyarakat, 2024)
Saving is the process of saving money for the long term. Therefore, an introduction to managing and managing finances needs to be implemented from an early age. One way that is implemented is by introducing savings to children at an early age. The aim of this outreach is also as a form of community service from KKL UIN SYAHADA Padangsidimpuan students to equip young children, especially at SD 22 Ranah Batahan, to understand the importance of saving, how to save, and also the benefits of savingThe method used is to provide counseling and socialize face to face. The result of this outreach is an increased understanding of elementary school students and girls about the culture of saving from an early age, this can be seen from the increasing interest of these children in starting to save both at home and at school